ORIGINAL PAPERThe association of 25-hydroxyvitamin D levels with secondary hyperparathyroidism in end-stage renal failure patients undergoing regular hemodialysis - Nasri, Hamid; Baradaran, Azar (Archives of Medical Science, 2005)
Introduction: To investigate the role of 25-OHD as a marker of nutrition and its association with mineral metabolism and serum parathormone secretion in end-stage renal failure patients undergoing regular hemodialysis (HD), a cross sectional study was carried out on a group of maintenance hemodialysis patients. Material and methods: Serum 25-hydroxy (25-OH vitamin D) levels, Intact serum PTH (iPTH) and also serum C-reactive protein(CRP), calcium, phosphorus and alkaline phosphatase (ALP) were measured. Results: In the study, significant differences of serum 25-OH vitamin D between diabetic and non-diabetics of male dialysis patients with more values in nondiabetic HD patients and a significant positive correlation of serum 25-OH vitamin D with BMI and also a near significant inverse correlation of serum 25-OH vitamin D with serum phosphorus were found, also a significant inverse correlation of serum 25-OH VitD with serum calcium was seen, too. Moreover, a weakly significant inverse correlation of serum 25-OH vitamin D with serum iPTH was seen, too. In this study no significant association between serum 25-OH vitamin D with serum albumin, CRP, ALP, dialysis adequacy and ages of the patients, duration and sessions of dialysis were found. Conclusions: In hemodialysis patients, low serum 25-OHD levels could be a risk factor for secondary hyperparathyroidism. Serum 25-OHD could show the nutritional status of HD patients. In dialysis patients, we suggest that the plasma levels of 25-OHD are maintained around the upper limit of the reference range of sunny countries.